Professional development schools : advances in community thought and research - Guadarrama, Irma N.; Ramsey, John M.; Nath, Janice L. (Research in professional development schools., 2005)
The collection of papers in this volume have a combined synergy that exudes a sense of hope and confidence that our progress in the Professional Development Schools research movement has been substantial and vibrant, even though some would argue that the strides are not enough nor fast enough to make a significant difference. However, no one can argue the fact that our efforts are indeed crucial to the improvement of education for all students and in that sense, Professional Development Schools Research is definitely on track.